Determinants of inpatient satisfaction at the wakatobi regency hospital - Muhammad Ansar Daud; Toni Wandra; Rinawati Sembiring; Daniel Ginting; Mido Ester Sitorus (Science Midwifery, 2023)
Patient satisfaction is an important indicator in health services in hospitals. One of the services provided by the hospital to serve the needs of the community is inpatient services. This study aims to determine the determinants of inpatient satisfaction at RSUD Wakatobi Regency, Southeast Sulawesi in 2022. This type of research is a quantitative study using a cross sectional study method. The population in this study were all patients who were hospitalized at the Wakatobi District Hospital for the period 3 June 2022 to 12 July 2022, the sample in the study was 208 people using total sampling from the entire population. The research instrument used a questionnaire which was analyzed using the SPSS application. then a Chi-Square Statistical test was carried out to see the relationship between these variables. The results of statistical analysis show the determinants of Tangible (p-value = 0.003), Reliability (p-value = 0.003), Responsiveness (p-value = 0.004), Assurance (p-value = 0.003), and Empathy (p-value = 0.004). Because the p-value α = 0.005, the alternative hypothesis is accepted, which means there is a significant relationship. The conclusion is that there is a significant relationship between the five determinant dimensions, namely Tangible, Reliability, Responsiveness, Assurance and Empathy with inpatient satisfaction at RSUD Wakatobi Regency Southeast Sulawesi. Suggestions for improvement for RSUD Wakatobi Regency, Southeast Sulawesi, should conduct periodic satisfaction surveys , so that input from patients and all visitors can be conveyed, and this can be a consideration for improving the quality of hospital services in the future.